"Of Thee We Sing": Microhistories of the Northeastern United States through the Lens of American Folkloric Opera. - Krenek, Christian. (2017)
Abstract: The folklore of the United States of America is, like its peoples, extremely multifaceted and complex, to the extent that singular statements about the entirety of this folklore are impossible to make. This thesis instead focuses on an extremely particular aspect of American folklore—operatic versions of the tales—from the Northeastern United States, specifically New York and New Hampshire. By analyzing, through a microhistorical and theatrical lens, how these folktales, and their operatic adaptations, change over time, it is possible to engage in a discussion of how this lore was used to shape Northeastern American identities throughout the nineteenth, twentieth, and twenty-first centuries.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of Drama.; Advisor: Heather Nathans.; Committee: Heather Nathans, Barbara Grossman, and Joseph Auner.; Keywords: Performing arts, Folklore, and Theater history.